2017
DOI: 10.1111/cns.12723
|View full text |Cite
|
Sign up to set email alerts
|

RNAi‐mediated ephrin‐B2 silencing attenuates astroglial‐fibrotic scar formation and improves spinal cord axon growth

Abstract: These results suggest that astroglial-fibrotic scar formation and particularly the expression of aggrecan and versican could be mitigated by ephrin-B2 specific siRNA, thus improving the microenvironment for spinal axon regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…EphrinB2 enhanced the TGF-β (Transforming Growth Factor-β) /Smad3 signaling-mediated cardiac fibrosis through regulating the interaction between Stat3 and Smad3 [ 15 ]. Interestingly, TGF-β also induced EphrinB2 expression in fibroblast, suggesting a positive feedback between EphrinB2 and TGF-β signaling [ 54 ]. Meanwhile, similar activation of EphrinB2 was observed in endothelial cells within TGF-β stimulation [ 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…EphrinB2 enhanced the TGF-β (Transforming Growth Factor-β) /Smad3 signaling-mediated cardiac fibrosis through regulating the interaction between Stat3 and Smad3 [ 15 ]. Interestingly, TGF-β also induced EphrinB2 expression in fibroblast, suggesting a positive feedback between EphrinB2 and TGF-β signaling [ 54 ]. Meanwhile, similar activation of EphrinB2 was observed in endothelial cells within TGF-β stimulation [ 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using a custom-made microfluidic platform containing chimeric ventral spinal cord 4.1 (VSC4.1) motoneurons, primary rat astrocytes and rat meningeal fibroblasts (MFb), they demonstrated that the administration of 30 nM of siRNA against ephrin-B2 complexed with SuperFectinTMII reagent (silencing efficiency ~84%) was able to ameliorate the effects of transforming growth factor-β1 (TGF-β1)-induced astroglial-fibrotic scar formation and enhance axonal growth of VSC4.1 motoneurons ( Figure 3 ). 120 …”
Section: Neuroglial Cells As Potential Targets Of Rnai For Nerve Injumentioning
confidence: 99%
“…(i, i′) Addition of TGF-β1 and ephrin B2-targeting siRNA enhanced length of VSC4.1 axons as compared to TGF-β1 alone. Adapted with permission from Y Li et al 120 (B) Increased neurite outgrowth on/in conditioned media (CM) from chondroitin polymerizing factor (ChPF)-targeting siRNA-treated Neu7 astrocyte cell line. Cerebellar granule neurons were either grown on a combination of poly-L-lysine (PLL), laminin (LAM) and immobilized CM (a, c) in half DMEM and half neurobasal (NB) + B27 or on a combination of PLL and LAM in half NB + B27 and half CM from the Neu7 cells (b, d).…”
Section: Neuroglial Cells As Potential Targets Of Rnai For Nerve Injumentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the loss of neurons, for example, due to aging processes, stroke, or traumatic brain injury (TBI), is mostly irreversible. The function of the degenerating neurons can be partially compensated by neighboring neurons, but astroglial‐fibrotic scar formation minimizes neuronal regeneration (Li et al, ).…”
Section: Progesterone and Prsmentioning
confidence: 99%